Pengemasan Dan Pemasaran Nata De Coco Produksi Rumah Tangga Sebagai Bentuk Pemberdayaan Lingkungan Dan Masyarakat Di Kelurahan Padang Matinggi Lestari - Pohan, rizky febriani (Jurnal Pengabdian Masyarakat, 2021)
Nata de coco is a product produced from the fermentation process of coconut water. Nata de coco is a health food that is rich in fiber, but low in calories. Nata de coco contains about 98% water, 0.2% fat, 0.012% calcium, 0.002% phosphorus and 0.0017% vitamin B3. This product has a high fiber content, including: cellulose, hemicellulose, lignin and water soluble fiber. The benefits of nata de coco for health include: lowering cholesterol, lowering blood glucose in diabetics, preventing constipation, controlling body weight (preventing obesity), preventing colon cancer and beneficial for the microflora in the large intestine. This nata de coco packaging and marketing training program is a training activity on how to properly and correctly package nata de coco and its marketing strategy so that the product increases consumer satisfaction. The participants of this training were partners and PKK women, Padang Matinggi Lestari Village, Padangsidimpuan Selatan District. The purpose of this nata de coco packaging and marketing training program is to provide knowledge to the community in Padang Matinggi Lestari Village, South Padangsidimpuan District,